Long-Term Mortality in HIV-Infected Individuals 50 Years or Older: A Nationwide, Population-Based Cohort Study. (1st February 2016) - Legarth, Rebecca A.; Ahlström, Magnus G.; Kronborg, Gitte; Larsen, Carsten S.; Pedersen, Court; Pedersen, Gitte; Mohey, Rajesh; Gerstoft, Jan; Obel, Niels
Abstract : Background: Although the prevalence of HIV-infection among individuals ≥50 years of age has increased, the impact of HIV-infection on risk of death in this population remains to be established. Our aim was to estimate long-term mortality among HIV-infected individuals who were 50 years or older, when compared with an individually-matched cohort from the background population. Methods: Population-based cohort-study including HIV-infected individuals ≥50 years, who were alive 1 year after HIV-diagnosis (n = 2440) and a comparison cohort individually-matched by age and gender extracted from the background population (n = 14, 588). Cumulative survival was evaluated using Kaplan–Meier method and Mortality Rate Ratios (MRRs) were estimated using Cox Regression Models. Study period 1996–2014. Results: Estimated median survival time from age 50 years for HIV-infected individuals increased from 11.8 years (95% CI: 10.2 to 14.5) during 1996–1999 to 22.8 years (20.0–24.2) in 2006–2014. MRR decreased with increasing age from 3.8 (3.1–4.7) for 50–55 years to 1.6 (1.0–2.6) for 75–80 years. In a cohort of well-treated HIV-infected individuals ≥50 years without AIDS-defining events or comorbidity at study inclusion (n = 517). MRR was 1.7 (1.2–2.3) compared with population controls without comorbidity. Conclusion: Among HIV-infected individuals estimated median survival time from age 50 years has increased by more than 10 years from 1996–1999 to 2006–2014, but is still substantially lower than in the background population. Even among well-treated HIV-infected individuals ≥50 years without comorbidity or AIDS-defining events the estimated median survival time remains lower than in the general population. Abstract : Supplemental Digital Content is Available in the Text.